Activity of selected glycosidases and availability of their substrates in bovine placenta during pregnancy and parturition with and without retained foetal membranes. Issue 9 (6th July 2020) - Jamioł, Monika; Wawrzykowski, Jacek; Mojsym, Wioleta; Hoedemaker, Martina; Kankofer, Marta
Abstract: The activity of glycosidases is crucial for the function and biological activity of proteins conjugated with sugar moieties, which play an important role in adhesion of cells during attachment and detachment of the foetal membranes. The aim of study was to describe the ability of bovine placental tissues to break down O‐glycosidic bonds in different glycoproteins by the determination of activity of β‐galactosidase, α‐l‐fucosidase, β‐ N‐ acetyl‐hexosaminidase and sialidase in early–mid‐pregnancy as well as at parturition with released and retained foetal membranes. Moreover, the availability of substrates for these glycosidases in placental homogenates was evaluated. Placental samples were collected from pregnant (2–4 months) cows in slaughterhouse ( n = 8) as well as during Caesarean section and divided into released foetal membranes ( n = 8) and retained foetal membranes ( n = 8). Tissue homogenates were subjected to spectrofluorimetric and spectrophotometric determinations of enzyme activities as well as electrophoretic separations. Enzyme activities expressed changes within examined time with significant ( p < .05) differences between pregnancy and physiological parturition in β‐ N‐ acetyl‐hexosaminidase and α‐l‐fucosidase in foetal part of placenta while in maternal part only in the latter one. Decreasing tendency in enzyme activity was noticed in foetal part of retained samples in comparison with released ones with significant ( p < .05) differences in α‐l‐fucosidase activity. The analysis of staining of sugar moieties attached to selected proteins depicted availability of sugar molecules in examined tissues, but their patterns differed between samples. In conclusion, sugar moieties in conjugated proteins express changes in the course of pregnancy which is reflected by the alterations in activities of placental glycosidases.